An extrapyramidal choreiform syndrome caused by amphetamine addiction. Issue 8 (August 1981) - Lundh, H; Tunving, K
Abstract : Four cases are described to demonstrate the extrapyramidal clinical syndrome sometimes appearing in chronic amphetamine users. The symptoms are dominated by choreiform or athetoid movements, ataxia and disturbances of gait. The syndrome develops during amphetamine abuse and may be observed also during abstinence. The symptoms usually disappear within a week when the drug is discontinued, but may remain for years.